Engineering Risk and Decision Analysis - , Okolie Paul Chukwulozie, Oluwadare Benjamin Segun, Okolie Uchenna Onyebuchi, Ugwuegbu Duke Chiagoro (Archives of Current Research International, 2018)
Engineering systems design and analysis is dependent on the ability to analyse the system in the context of uncertainties in their performance. Engineering systems design evaluates the reliability of normal operations, the risk of normal operations, appropriate decisions to maintain reliability and optimal performance. Many industries are scouting and employing engineering professionals with appropriate understanding and knowledge of engineering systems design and risk management. This will significantly increase the number of engineers with the professional skills in engineering systems design and risk management in engineering. This research reveals in details the areas of risk assessment, risk management, decision and engineering analysis. Risks have been identified. The decisions to be taken to avoid such risk from occurring have been provided by bringing in advanced analytic techniques. Employment of the appropriate advanced analytical techniques and professionals in the system will advance decision making and risk assessment and consequently risk management.